Azygos vein lacerations, a rare injury from high-impact chest trauma: Two cases and a review of the literature. (February 2022) - Li, Christine; Martin, Katherine; Read, David
Abstract: Introduction: Thoracic trauma is a significant cause of mortality, being responsible for 25% of trauma deaths. Despite this, azygos vein lacerations are rare, with only 35 published cases. We present two cases of azygos vein laceration over 21 years from 1999 to 2020 at a Level One Trauma Centre in Melbourne, Australia, as well as a review of the literature. Case presentations: The first case is a 38-year-old male who fell eight metres from a motorbike jump. He arrived in our emergency department in extremis. The second case is an 81-year-old female driver who presented following a motor vehicle crash. Both patients had massive right haemothorax and haemodynamic instability, so were transferred to the operating theatre for emergency thoracotomies. Both patients survived to hospital discharge. Discussion: Of the 37 cases of azygos vein injury, including our two, 36 were due to blunt trauma and one from penetrating trauma. Sixteen survived to hospital discharge, producing a 43% mortality rate. Only one of these survivors was managed non-operatively, the remainder underwent emergency thoracotomy and azygos vein ligation. The mortality rate reduced to 31% in those who underwent thoracotomy ( n = 29). Presentation was predominantly with shock (83%) and right hemithorax white-out on chest x-ray (81%). Conclusion: Azygos vein injuries are a rare but important cause of thoracic haemorrhage in high-impact blunt trauma. They are often fatal, so management relies on expedient transfer to theatre. Highlights: Traumatic azygos vein injury is extremely rare, but often fatal. Must be considered in a hypotensive patient with right hemithorax white-out on CXR. Treatment relies on urgent surgery. A number of thoracotomy approaches have been successful.